MICROSTRUCTURE AND PHASE OF POLY(VINYLIDEN FLUORIDE) FILMS BY ELECTROPHORETIC DEPOSITION: EFFECT OF POLYMER DISPERSION’S STIRRING CONDITIONS - Lau, Kok Tee; Mohd Suan, Mohd Shahadan; Zaimi, M.; Abd Razak, Jeefferie; Azam, M.A.; Mohamad, N. (Journal of Advanced Manufacturing Technology (JAMT), 2016)
Electrophoretic deposition (EPD) technique had been applied to conformally deposit piezoelectric PVDF film on the uneven surface target. Nevertheless, optimization of polymer dispersion preparation process is crucial to achieve an even and uniform PVDF film. Sedimentation test showed PVDF polymer dispersions are more stable and well-dispersed in DMF than in MEK. Higher stirring temperature and shorter stirring time in MEK further decreased the PVDF dispersion stability and produced higher degree of agglomerated PVDF chain. As a result, MEK-based dispersion produced thick and fully coverage films,. Whereas, the DMF-based dispersions produced thin but partial coverage films. Thus, the degree of dispersibility of the PVDF dispersions has a profound influence on the deposited films’ microstructure. FTIR spectra indicates presences of electroactive b phase in DMF-derived deposit, and mixture of a and b phases in the MEK-derived films.